Stem borers revisited: Host resistance, tolerance, and vulnerability determine levels of field damage from a complex of Asian rice stemborers - Horgan, Finbarr G.; Romena, Angelita M.; Bernal, Carmencita C.; Almazan, Maria Liberty P.; Ramal, Angelee Fame (Elsevier, 2021)
Yield losses from rice stem borers depend on the nature of the rice variety, the timing of attack, and the composition of the stem borer species assemblage. This study uses a range of phenotyping methods to distinguish different categories of herbivore-rice interaction that determine relative damage levels (dead heart and whitehead-panicles) and yield losses to varieties exposed to stem borers. Phenotyping studies were conducted in a greenhouse, screen house and field using two stem borer species (Scirpophaga incertulas [yellow stem borer - YSB] and Chilo suppressalis [striped stem borer - SSB]) and 12 rice lines. Only YSB displayed oviposition preferences across rice varieties. Both stem borer species performed better (greater survival, shorter development times, heavier pupae) on rice at vegetative compared to reproductive growth stages, and SSB was less capable than YSB of developing on rice at reproductive growth stages. Stem borer larval survival, body weight, development time, and tiller damage across different rice varieties in greenhouse experiments was poorly correlated between the two stem borer species and for each of the species on rice at two different plant growth stages (vegetative and reproductive). In contrast, rice tillering and yield responses to the two stem borer species were often highly correlated, but only when plants were attacked at the reproductive stage. Short-term, controlled experiments revealed aspects of host resistance and relative changes in plant biomass and yield in response to damage (condition change). However, the results from controlled environments and field-plots were not generally correlated because plant vulnerability, i.e., relative exposure to stem borer attack due to crop duration, largely determined field damage. We recommend that phenotyping studies should differentiate between the resistance, tolerance and vulnerability of rice lines to complexes of stem borers in a given region. Single stem borer species experiments under controlled environments are useful to gain knowledge of the nature of rice-stem borer interactions; however, field testing with comparative treatments, particularly under high soil fertilizer levels that increase plant attractiveness, are better for assessing the relative propensities of rice varieties to incur damage and yield losses due to complexes of stem borers.